Production Division Compliance Audit On Standard Operating Procedures Pt Pusaka Marmer Indah Raya (Pumarin) - Aisyah Margaretta; Tommy Kuncara (International Journal of Science, Technology & Management, 2021)
This study aims to determine whether the employees of the production division have complied with the standard operating procedures set by PT PUSAKA MARMER INDAH RAYA (PUMARIN) properly or not. The method used in this scientific research is a qualitative descriptive analysis technique, which is a research technique that analyzes, describes, and summarizes various conditions, situations from various data collected in the form of the results of interviews or observations about the problems studied that occur in the field. The results of the research that the authors found were that there were two points that were still not adhered to by the production division employees, such as not smoking in all areas of the work environment, and correctly understanding the materials that would be used for production.